Da imunidade religiosa no Brasil: perspectiva no direito tributário - Mesquita Filho, Luiz (2014)
Brazil is a secular country, and has adopted this condition since the Republican period, which began with the 1891 Constitution. Since 1946, religious immunity has been assured to the temples of any belief, which means that churches are free of charge taxes on its assets and income tied to their core activities. Considering the above, this study discusses issues related with religious immunity, from religious secularism, with examination of Brazilian constitutions and related legislation on the subject, focusing tax administration, including the supervision and law execution.